Pemanfaatan Kotoran Ternak dan Masa Panen yang Berbada terhadap Tingkat Pertumbuhan dan Biomassa Cacing Sutra (Tubifex sp). - Belo, Jitro Michdonia Mina; Salosso, Yuliana; Dahoklory, Nicodemus (Nusa Cendana University, 2024)
The research was conducted at the Lewa Fish Seed Center (BBI), Lewa District, Lewa Paku Village, East Sumba Regency, East Nusa Tenggara Province for 30 days. Completely Randomized Design (CRD) as the method used with research variables in the form of differences in harvest time consisting of 3 (three) treatments and replicates. The treatments in this study include Treatment A harvest day 10, Treatment B harvest day 20, Treatment C harvest day 30. Parameters observed in this study were absolute weight, biomass and water quality. The absolute biomass increase of silk worms (Tubifex sp.) from the results of this study was highest in treatment C (30th day harvest time) which was 50.7 g/container, followed by treatment B (20th day harvest time) 30.3 g/container and treatment A (10th day harvest time) 7.0 g/container. The longer the harvest period, the more the results obtained. The length of harvest time that produces silk worms (Tubifex sp.) with optimal protein content from the results of this study is in treatment B (20th day harvest time) which is 49.781%, followed by treatment C (30th day harvest time) 41.611% and treatment A (10th day harvest time) 40.347%. Keywords: Absolute weight, biomassa, silk worm